Propuesta de mejora del proceso de almacenamiento de la empresa alimentos Food Service SAS (2023)
In the present work, a diagnosis of the storage process of the company Alimentos Food Service SAS was developed. Different diagnostic techniques were applied to characterize the storage process, once the main problems were determined, strategies were designed to improve the process, among which the creation of a new position for the safe storage of the products stands out. timely control of inventories, readiness for dispatch and billing of products. Within this research proposal, a financial evaluation of the different strategies proposed is carried out.